The Role of Mesenchymal Stem Cells in Regulating Astrocytes-Related Synapse Dysfunction in Early Alzheimer’s Disease - Liu, Cong (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD), a neurodegenerative disease, is characterized by the presence of extracellular amyloid-β (Aβ) aggregates and intracellular neurofibrillary tangles formed by hyperphosphorylated tau as pathological features and the cognitive decline as main clinical features. An important cellular correlation of cognitive decline in AD is synapse loss. Soluble Aβ oligomer has been proposed to be a crucial early event leading to synapse dysfunction in AD. Astrocytes are crucial for synaptic formation and function, and defects in astrocytic activation and function have been suggested in the pathogenesis of AD. Astrocytes may contribute to synapse dysfunction at an early stage of AD by participating in Aβ metabolism, brain inflammatory response, and synaptic regulation. While mesenchymal stem cells can inhibit astrogliosis, and promote nonreactive astrocytes. They can also induce direct regeneration of neurons and synapses. In this review, we describe the role of mesenchymal stem cells and underlying mechanisms in regulating astrocytes-related Aβ metabolism, neuroinflammation and synapse dysfunction in early AD, exploring the open questions in this field.